EXPERIMENTAL RESEARCH OF THE ANCHOR SCREWS FIXATION STRENGTH INTO THE HUMERAL HEAD USED FOR THE SHOULDER HANGING TO THE ACROMION FOR THE RECURENT SHOULDER DISLOCATION TREATMENT - Suhin, Yu. V.; Logay, V. A.; Danilov, P. V.; Lazareva, D. V. (Journal of Education, Health and Sport, 2015)
Suhin Yu. V., Logay V. A., Danilov P. V., Lazareva D. V. Експеріментальне дослідження міцності фіксації анкерного гвинту в голівці плечової кістки, використовуване для підвішування плеча до акроміону при лікуванні звичного вивиху плеча = Experimental research of the anchor screws fixation strength into the humeral head used for the shoulder hanging to the acromion for the recurent shoulder dislocation treatment. Journal of Education, Health and Sport. 2015;5(12):289-298. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35434 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A289-298 http://pbn.nauka.gov.pl/works/681685 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.11.2015. Revised 25.11.2015. Accepted: 14.12.2015. УДК: 616.717.41-089.28 ЕКСПЕРІМЕНТАЛЬНЕ ДОСЛІДЖЕННЯ МІЦНОСТІ ФІКСАЦІЇ АНКЕРНОГО ГВИНТУ В ГОЛІВЦІ ПЛЕЧОВОЇ КІСТКИ, ВИКОРИСТОВУВАНЕ ДЛЯ ПІДВІШУВАННЯ ПЛЕЧА ДО АКРОМІОНУ ПРИ ЛІКУВАННІ ЗВИЧНОГО ВИВИХУ ПЛЕЧА EXPERIMENTAL RESEARCH OF THE ANCHOR SCREWS FIXATION STRENGTH INTO THE HUMERAL HEAD USED FOR THE SHOULDER HANGING TO THE ACROMION FOR THE RECURENT SHOULDER DISLOCATION TREATMENT Ю. В. Сухін[1], В. А. Логай[1], П. В.Данілов[2], Д. В. Лазарєва[3] Yu. V.Suhin[1], V. A. Logay[1], P. V. Danilov[2], D. V. Lazareva[3] [1]Одеський національний медичний університет, м. Одеса; [2]Національний технічний університет України «Київський політехнічний університет», м. Київ; [3]Одеський національний політехнічний університет, Одеса [1]Odessa National Medical University, Odessa; [2]Ukrainian National Technical University “Kyiv Polytechnic University”, Kyiv; [3]Odessa National Polytechnic University, Odessa Summary The article highlights the results of the experiment, which is a major step in the proposed original method of treatment recurrent shoulder dislocation. The strength of the anchor screw fixation in the humerus head and an optimal angle of its introduction is the main characteristic of the reliability of this method of treatment recurrent shoulder dislocation. This method of treatment allows to minimize volume of operation, to reduce operational risk and to avoid the recurrence of dislocation in the future completely. Кey words: recurrent shoulder dislocation, minimally invasive surgery, the strength of fixing the anchor screws, introductions angle of anchor. Резюме У статті висвітлено результати експерименту, які є основним етапом у запропонованій оригінальній методиці лікування звичного вивиху плеча. Міцність фіксації анкерного гвинта в голівці плечової кістки та оптимальний кут його введення є основними характеристиками надійності розробленого методу лікування вказаної патології. Розроблений метод лікування дозволяє мінімізувати обсяг оперативного втручання, зменшити операційний ризик і повністю уникнути рецидивів вивиху у подальшому. Ключові слова: звичний вивих плеча, малоінвазивне оперативне лікування, міцність фіксації анкерного гвинта, кут введення анкеру. Резюме ЭКСПЕРІМЕНТАЛЬНОЕ ИССЛЕДОВАНИЕ ПРОЧНОСТИ ФИКСАЦИИ АНКЕРНОГО ВИНТА В ГОЛОВКЕ ПЛЕЧЕВОЙ КОСТИ, ИСПОЛЬЗУЕМОЕ ДЛЯ ПОДВЕШИВАНИЯ ПЛЕЧА К АКРОМИОНУ ПРИ ЛЕЧЕНИИ ПРИВЫЧНОГО ВЫВИХА ПЛЕЧА. В статье приведены результаты эксперимента, которые являются основным этапом в предложенной оригинальной методике лечения привычного вывиха плеча. Прочность фиксации анкерного винта в головке плечевой кости и оптимальный угол его введения являются основными характеристиками надёжности разработанного метода лечения указанной патологии. Разработанный метод лечения позволяет минимизировать объем оперативного вмешательства, снизить операционный риск и полностью избежать рецидивов вывиха в дальнейшем. Ключевые слова: привычный вывих плеча, малоинвазивное оперативное лечение, прочность фиксации анкерного винта, угол введения анкера.